HUBUNGAN MUTU PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN DI POLI THT RSUD MUARA TEWEH - Hanimah, Sapmiati; Basit, Mohammad; Wijaksono , Muhammad Arief; Widodo , Hariadi (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2025)
High patient volume at the Otorhinolaryngology (ENT) polyclinic is driven by expectations for health improvement and satisfactory service delivery. Service quality is a critical factor for patients and a key competitive advantage for healthcare facilities, making its assessment essential. This study aimed to identify the relationship between healthcare service quality and patient satisfaction at the ENT Polyclinic of Muara Teweh Regional Hospital. This study employed a quantitative method with a correlational design, recruiting 62 respondents through accidental sampling. Data were analyzed using univariate analysis and the Spearman Rank correlation test. The results indicated that a vast majority of patients perceived the service quality as poor (93.5%) and reported dissatisfaction (71.0%). Specifically, the service quality dimensions receiving the most negative evaluations were empathy and tangibles. Bivariate analysis revealed a strong and statistically significant correlation between healthcare service quality and patient satisfaction (p=0.001<0.05). This finding underscores that service quality, particularly concerning interpersonal interactions and physical facilities, is a significant predictor of patient satisfaction at the ENT Polyclinic of Muara Teweh Regional Hospital.